Pengaruh Tingkat Kesejahteraan, Lingkungan Kerja Fisik dan Kepemimpinan Terhadap Semangat Kerja Karyawan Villa The Akasha Beach Estate - Prawira, Made Satya; Riana, I Gede (E-Jurnal Manajemen; Vol 3 No 9 (2014), 2014)
Normal 0 false false false EN-US X-NONE X-NONE ABSTRACT This study aims to determine the effect of the level of well being , physical work environment , and leadership simultaneously on employee morale at The Akasha Villa Beach Estate , to determine the effect of the level of well being , physical work environment , and partially to the spirit of leadership The employees working at the villa Akasha Beach Estate . This research was conducted at The Akasha Villa Beach Estate with data analysis techniques of multiple linear regression . The number of samples obtained by using census method is as much as 45 respondents . Based on the analysis it can be concluded that the level of well being , physical work environment , and a positive and significant effect of leadership both simultaneously and partially on employee morale , it can be proved from the value of t is greater than t table . Keywords : Welfare , Physical Work Environment , Leadership and Morale